2019
DOI: 10.1021/acs.orglett.9b03038
|View full text |Cite
|
Sign up to set email alerts
|

n-Pentenyl-Type Glycosides for Catalytic Glycosylation and Their Application in Single-Catalyst One-Pot Oligosaccharide Assemblies

Abstract: We have developed a new type of n-pentenyl-type glycosides that can be activated by catalytic amounts of promoter, Hg­(NTf2)2 or PPh3AuCl/AgNTf2, at room temperature. The mild activation conditions and outstanding stability of common protection/deprotection manipulations enable the enynyl donors to have broad applications in constructing various glycosidic bonds. Furthermore, under the Hg­(NTf2)2-catalyzed conditions, the sequential activation of different types of donors was achieved, based on which a gentiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…It was observed that an excess of the reagent delivered a more polar product within 15 min, which correspondingly underwent acetylation (Scheme ). The formation of monoacetate compound 28 was confirmed by NMR and HRMS data, which were found to be in complete accordance with a literature-reported compound . Thus, it was concluded that under Birch reduction, CNMe ether can be selectively deprotected in the presence of more robust benzyl ether and acid-sensitive acetal protections to act as an orthogonal PG.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…It was observed that an excess of the reagent delivered a more polar product within 15 min, which correspondingly underwent acetylation (Scheme ). The formation of monoacetate compound 28 was confirmed by NMR and HRMS data, which were found to be in complete accordance with a literature-reported compound . Thus, it was concluded that under Birch reduction, CNMe ether can be selectively deprotected in the presence of more robust benzyl ether and acid-sensitive acetal protections to act as an orthogonal PG.…”
Section: Resultssupporting
confidence: 85%
“…The formation of monoacetate compound 28 was confirmed by NMR and HRMS data, which were found to be in complete accordance with a literature-reported compound. 16 Thus, it was concluded that under Birch reduction, CNMe ether can be selectively deprotected in the presence of more robust benzyl ether and acid-sensitive acetal protections to act as an orthogonal PG. This feature can be promising in the synthesis of C2-linked saponins where CNMe ether may be employed as a temporary PG.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trichloroacetimidate leaving group was successfully activated by FeCl 3 , 15b which may be more Lewis acidic compared to the ferrocenium complexes employed herein. On the other hand, an npentenyl leaving group was previously proven to also not be activated by Fe(CF 3 SO 3 ) 3 , 23 which may be due to the low affinity of Fe(III) to isolated double bonds, through which the leaving group may be activated. The mode of activation is currently In the presence of 100 mol% promoter, only 42% isolated yield were obtained, and hydrolysis was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Glycosidation is the key reaction for the chemical synthesis of numerous oligosaccharides and glycoconjugates with significant bioactivities. , To tackle the construction of various types of challenging glycosidic linkages that exist in naturally occurring oligosaccharides and glycoconjugates, alkyne-based glycosyl donors have attracted great attention in the past 15 years. Among the glycosidation that employs alkyne-based glycosyl donors, the triple bonds are usually activated by a catalytic amount of gold complex . Especially, the Yu glycosidation that utilizes glycosyl ortho -alkynylbenzoates as donors and gold­(I) complexes as catalysts has been extensively investigated and broadly applied to the synthesis of a wide variety of glycans and glycoconjugates. ,, …”
Section: Introductionmentioning
confidence: 99%